How Accountable is Zakat Management in Indonesia? An Evidence from BAZNAS of North Sulawesi - Nur Fitry Latief; Nur Shadiq Sandimula (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
This study was motivated by some zakat management accountability issues discovered in preliminary studies conducted in several zakat agencies throughout the North Sulawesi province. This study investigates zakat management accountability in three chapters/sub-chapters of the National Zakat Agency (Badan Amil Zakat Nasional – BAZNAS) in North Sulawesi province: the BAZNAS provincial chapter, the BAZNAS of Manado City sub-chapter, and the BAZNAS of Kotamobagu City sub-chapter. Data were collected using documentation studies and in-depth interviews with zakat administrators from the zakat institutions using purposive and snowball sampling techniques. To analyze the data, this study employed an Action Research (AR) approach, while the results were interpreted using a four-stage qualitative analysis: domain analysis, taxonomic analysis, componential analysis, and theme analysis. The findings indicate that zakat management in the targeted institutions has not fully met the accountability standard outlined in Law No. 23/2011, specifically in terms of 1) the absence of certain accountability indicators, 2) inefficient use of websites, 3) ineffective use of social media, and 4) the absence of an internal audit unit (SAI). The findings have implications for improving BAZNAS in North Sulawesi province and throughout Indonesia. In particular, this study suggests optimizing institution websites and social media by integrating them with provincial zakat institutions. Consequently, it is crucial to employ an IT expert who specializes in in-out information from/to society. The establishment of SAI and the employment of shariah auditors are also noteworthy. Collaboration with Islamic universities could be a first step towards a solution.==================================================================================================== ABSTRAK – Seberapa Akuntabelkah Pengelolaan Zakat di Indonesia? Kajian pada BAZNAS Sulawesi Utara. Kajian ini dilatarbelakangi oleh beberapa persoalan akuntabilitas pada pengelolaan zakat di beberapa BAZNAS dalam lingkungan provinsi Sulawesi Utara. Tulisan ini bertujuan untuk mengkaji akuntabilitas pada tiga BAZNAS di provinsi Sulawesi Utara, yaitu BAZNAS provinsi, BAZNAS Kota Manado, dan BAZNAS Kota Kotamobagu. Selain dari studi dokumentasi, data juga dikumpulkan melalui wawancara mendalam administrator zakat dari ketiga BAZNAS terkait yang dipilih berdasarkan teknik sampling purposif dan bola salju (snowball). Untuk menganalisis data, kajian ini menggunakan metode Action Research (AR), yang kemudian diinterpretasikan dalam empat tahapan analisis, yaitu analisis domain, analisis taksonomi, analisis komponensial, and analisis tema. Kajian ini menemukan bahwa pengelolaan zakat di objek penelitian tersebut belum sepenuhnya memenuhi kriteria akuntabilitas sebagaimana disebutkan dalam UU No. 23/2011, terutama dalam hal: 1) kealpaan dari dari beberapa indikator akuntabilitas, 2) websitenya belum optimal, 3) sosial media belum dimanfaatkan dengan baik, dan 4) ketiadaan dari satuan pengawasan internal. Hasil kajian ini berimplikasi pada perbaikan institusi BAZNAS di Sulawesi Utara secara khusus dan Indonesia secara umum. Kajian ini merekomendasikan adanya optimalisasi website dan media sosial dengan pengintegrasian ke dalam website BAZNAS provinsi. Oleh karenanya, diperlukan seorang profesional di bidang IT yang khusus mengelola segala informasi dari luar ke dalam dan sebaliknya. Selain itu, membangun sistem pengawasan internal dengan merekrut tenaga audit syariah juga sangat penting. Pada tahap awal, hal ini dapat dilakukan melalui kerjasama dengan PTKIN.